Finding Opportunity in Co-Teacher Personality Conflicts - Boyer, Kara; McMillen, Cory (Journal of the American Academy of Special Education Professionals, 2012)
Co-teaching, the collaborative instruction of an inclusive classroom by a general education and special education teacher, is a relatively new construct. As a result, many of the pitfalls and struggles associated with it are still being defined, and solutions are often hard to come by. Disagreements, and especially large-scale personality conflicts, can be detrimental to student achievement. Having addressed that problem during our first few years through the development of pedagogical strategies, we offer other co-teachers a series of techniques and activities that can allow them to circumvent their own personality clashes.